(untitled) (Fiep Bulletin - online, 2015)
Cardiac arrest, commonly called PCR, is considered the most serious cardiac emergency, characterized as the absence of cardiac mechanical activity, which is confirmed by the absence of pulse, apnea or gasping and also for lack of responsiveness of the victim. Although in recent years, advances have occurred regarding the prevention and treatment of PCR, it still remains a problem of public health worldwide and many lives are lost every year in Brazil. Grounded for these reasons, the following question arises: which knowledge of a group of nursing students about PCR?. This is a descriptive study with quantitative approach, performed in the Department of Integrated Colleges of Nursing Ducks, the research sample was consistituida by 144 nursing students, the study was approved by the Ethics Committee in Research of FIP in the opinion 31140614.2 .0000.5181 to collect data from a screenplay structured interview was used. As a result 83% of respondents were female, 71% were aged between 20 and 30 years, 56% do not have other technical or college degree, 68% said they were aware of the techniques of PCR, 68% responded to recognize an individual in PCR, as the chain of survival 51% reported knowing, 55% never attended a course aimed at serving victims of PCR and 94% reported having interest in the area. It was found that the research objective was achieved because, through research it was found that nursing students have significant knowledge about Cardiopulmonary Resuscitation and also on the procedures to be followed for proper care of victims PCR, with emphasis on the maneuvers of Cardiopulmonary Resuscitation.